Influence of added gelatin on the rheological properties of a Fucus vesiculosus extract. (June 2019) - Voron'ko, Nicolay G.; Derkach, Svetlana R.; Kuchina, Yuliya A.; Sokolan, Nina I.; Kuranova, Lyudmila K.; Obluchinskaya, Ekaterina D.
Abstract: The influence of gelatin from bovine skin on the rheological properties of hydrogels in an extract from the alginate-containing algae Fucus vesiculosus was studied. The shear rate and dynamic mechanical analyses were used to determine the rheological properties. FT-IR spectroscopy showed that the main structural component of the Fucus extract was sodium alginate. The changes of the rheological properties of the extract with the introduction of gelatin are explained using the framework of the alginate–gelatin complexation model. The Fucus extract showed a weakly expressed non-Newtonian behaviour since the flow index in the Ostwald–De Waele equation is 0.91–0.94. The introduction of gelatin (1.0 wt.%) into the extract at 24 °C led to the formation of a hydrogel, whereas the extract itself cannot form a gel with these conditions. Further increasing the concentration of gelatin led to an exponential increase in the yield stress, plastic viscosity and apparent viscosity of the hydrogels. The introduction of gelatin into the Fucus extract at 4 °C led to a non-additive increase in the elastic modulus ( G ′), and a decrease in the tan δ of the hydrogels, i.e., strengthening of the elastic properties and weakening of viscous properties in these systems. The changes in the rheological parameters of a Fucus extract after the introduction of gelatin can be explained by an increase in the concentration of triple helices in the macromolecular chains of the gelatin, which are the elastic elements in the 3D mixed gel network.